E-research and technological research competence in teacher training - Zapata Ancajima, Juan Carlos (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The research was outlined with the objective of determining if the implementation of an e-research proposal strengthens the technological investigative competence in students of a master’s degree in Educational Sciences from a public university in Peru. It was developed with a quantitative approach, pre-experimental design with pre-test/post-test in a single group, with a sample of 30 students, in whom was measured the level of knowledge and implementation of six groups of useful digital tools in the preparation of a thesis. In the results, it was concluded that the technological investigative competence was strengthened through e-research training experiences.